2022
DOI: 10.1038/s41467-022-33500-9
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the frontotemporal dementia gene GRN results in gangliosidosis

Abstract: Haploinsufficiency of GRN causes frontotemporal dementia (FTD). The GRN locus produces progranulin (PGRN), which is cleaved to lysosomal granulin polypeptides. The function of lysosomal granulins and why their absence causes neurodegeneration are unclear. Here we discover that PGRN-deficient human cells and murine brains, as well as human frontal lobes from GRN-mutation FTD patients have increased levels of gangliosides, glycosphingolipids that contain sialic acid. In these cells and tissues, levels of lysosom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 55 publications
8
79
2
Order By: Relevance
“…GRN mutations are proposed to disrupt lysosomal homeostasis, and hypomyelination is common to many lysosomal storage diseases, including neuronal ceroid lipofuscinosis (NCL) caused by homozygous GRN mutations [ 11 , 12 ]. Reduced GCase activity has been reported in G rn-/- mice [ 19 , 43 ], IPSC-derived neurons [ 18 ] and brain tissue from FTD- GRN cases [ 44 , 45 ]. We observed no significant difference in GCase activity between FTD cases and controls, in frontal grey or white matter, or parietal white matter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GRN mutations are proposed to disrupt lysosomal homeostasis, and hypomyelination is common to many lysosomal storage diseases, including neuronal ceroid lipofuscinosis (NCL) caused by homozygous GRN mutations [ 11 , 12 ]. Reduced GCase activity has been reported in G rn-/- mice [ 19 , 43 ], IPSC-derived neurons [ 18 ] and brain tissue from FTD- GRN cases [ 44 , 45 ]. We observed no significant difference in GCase activity between FTD cases and controls, in frontal grey or white matter, or parietal white matter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics also identified dysregulation of glycerolipid catabolism in the FTD patient ineurons, and our results are consistent with other proteomics studies using mouse models of PGRN-deficiency. Both Huang et al (2020) 47 and Boland et al (2021) 48 found changes in proteins associated with lipid catabolism in Grn-deficient mouse brain samples 47,48 . We found reduced levels of lysosomal acid lipase (LIPA), which is involved in the hydrolysis of cholesterol esters and triglycerides to release cholesterol and fatty acids, in the PGRN-deficient FTD i-neurons.…”
Section: Discussionmentioning
confidence: 96%
“…The lipidomic profiles in brains of Grn R493X/ R493X mice resemble lipidomic changes in FTD-GRN [120]. Levels of monosialyated-GM1 and di-sialylated GD1 species are significantly elevated in brain tissue from patients with FTD-GRN but not in brain tissue from patients with sporadic-non-GRN FTD [120]. Finally, Grn R493X/R493X mice also exhibit cytoplasmic accumulation of TDP43 and a dramatic reduction in synaptophysin [126].…”
Section: R493x Knock-in Micementioning
confidence: 90%
“…Also, like Grn -/mice, Grn R493X/R493X mice have age-dependent accumulation of ganglioside species mono-sialylated GM1 and di-sialylated GD-3 in areas of the cortex, further supporting the idea that progranulin deficiency impairs sphingolipid degradation. The lipidomic profiles in brains of Grn R493X/ R493X mice resemble lipidomic changes in FTD-GRN [120]. Levels of monosialyated-GM1 and di-sialylated GD1 species are significantly elevated in brain tissue from patients with FTD-GRN but not in brain tissue from patients with sporadic-non-GRN FTD [120].…”
Section: R493x Knock-in Micementioning
confidence: 90%
See 1 more Smart Citation